Familial Clustering of Gastric Cancer: A Retrospective Study Based on the Number of First-Degree Relatives. Issue 20 (May 2016) - Choi, Yoon Jin; Kim, Nayoung; Jang, Woncheol; Seo, Bochang; Oh, Sooyeon; Shin, Cheol Min; Lee, Dong Ho; Jung, Hyun Chae
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This comprehensive cross-sectional study aimed to identify factors contributing to familial aggregation of gastric cancer (GC). A total of 1058 GC patients and 1268 controls were analyzed separately according to the presence or absence of a first-degree relative of GC (GC-relative). Logistic regression analysis adjusted for age, gender, residence during childhood, smoking, alcohol intake, monthly income, spicy food ingestion, Helicobacter pylori status and host cytokine polymorphisms was performed. Cytotoxin-associated gene A ( cagA ) positivity was a distinctive risk factor for GC in the family history (FH)-positive group (odds ratio [OR], 2.39; 95% confidence interval [CI], 1.42–4.00), while current/ex-smoker, moderate to strong spicy food ingestion, and non-B blood types were more closely associated with GC in the FH-negative group. Among the FH-positive group, alcohol consumption showed a synergistic carcinogenic effect in the at least 2 GC-relatives group compared to the 1 GC-relative group (1.71 vs. 9.58, P for interaction = 0.026), and this was dose-dependent. In the subjects with ≥2 GC-relatives, TGFB1 -509T/T was a risk factor for GC (OR 23.74; 95% CI 1.37–410.91), as were rural residency in childhood, alcohol consumption, spicy food ingestion, and cagA positivity. These results suggest that subjects with FH may be a heterogeneous group in terms of gastric cancer susceptibility. Especially, subjects with ≥2 GC-relatives should undergo risk stratification including TGFB1 -509T/T and alcohol consumption.